Detection of emerging genotypes in Trichophyton mentagrophytes species complex: A proposal for handling biodiversity in dermatophytes - Tang, Chao; Ahmed, Sarah A.; Deng, Shuwen; Zhang, Lu; Zoll, Jan; Al-Hatmi, Abdullah M. S.; Meis, Jacques F.; Thakur, Rameshwari; Kang, Yingqian; de Hoog, G. Sybren (Frontiers in Microbiology, 2022)
A resistant and hypervirulent dermatophytes from India has been described as a taxonomic novelty, Trichophyton indotineae, a species of the Trichophyton mentagrophytes complex. Rapid detection and correct identification of closely similar dermatophytes with different predilections are essential for efficient clinical management. We evaluated the efficacy of rapid diagnostic methods of clinical and environmental strains in the Trichophyton mentagrophytes complex. The methods included Realtime-PCR, DermaGenius, LAMP, and MALDI-ToF MS, using rDNA ITS sequences as taxonomic standard. The results show that only MALDI-ToF MS can distinguish 96.97% Trichophyton indotineae from other closely related species. The complex comprises numerous clones which may differ in anonymous markers but with similar evolutionary behavior. Therefore, we recommend to distinguish species only when they show an appreciable degree of adaptation and thus are clinically significant. The distinction of remaining clonal diversity is an epidemiological query and can be solved by haplotype numbering.